1996
DOI: 10.1006/hbeh.1996.0002
|View full text |Cite
|
Sign up to set email alerts
|

Social Modulation of Sex Steroid Concentrations in the Urine of Male Cichlid FishOreochromis mossambicus

Abstract: The relationship between urinary concentrations (free / of the teleost families in which there is a larger body sulfates / glucuronides) of the steroids testosterone (T), of evidence in the role of androgens on the control of 11-ketotestosterone (11KT), 17a, 20b-dihydroxy-4-pregmale social behavior, both in terms of organization nen-3-one (17,20b-P) and 17a,20a-dihydroxy-4-preg- (Billy and Liley, 1985;Groothuis and Ros, 1993) trated and intact fish have been the primary tools toSimilar relationships were foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
120
2
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 182 publications
(131 citation statements)
references
References 54 publications
8
120
2
1
Order By: Relevance
“…major reduction in circulating androgen levels further supports a key role for androgens produced in the testis in the linkage between gonadal maturation and the expression of reproductive behavior. The lack of effects of castration on aggressive behaviors apparently contrasts with previous studies in this species where circulating androgens have been shown to be correlated with dominant behavior (Oliveira et al, 1996) and to mediate experiencedependent effects on male competitive behavior . However, these apparently contradictory results can be explained by androgens playing either a mediator or a moderator role in the regulation of aggressive behavior, since only a mediator role would predict androgens to be necessary and sufficient.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…major reduction in circulating androgen levels further supports a key role for androgens produced in the testis in the linkage between gonadal maturation and the expression of reproductive behavior. The lack of effects of castration on aggressive behaviors apparently contrasts with previous studies in this species where circulating androgens have been shown to be correlated with dominant behavior (Oliveira et al, 1996) and to mediate experiencedependent effects on male competitive behavior . However, these apparently contradictory results can be explained by androgens playing either a mediator or a moderator role in the regulation of aggressive behavior, since only a mediator role would predict androgens to be necessary and sufficient.…”
Section: Discussioncontrasting
confidence: 99%
“…In our lab we have been using the Mozambique tilapia (Oreochromis mossambicus) as a model to study the neuroendocrinology of social behavior. In this species androgens respond to social interactions (Oliveira et al, 1996) and socially driven changes in androgens moderate the expression of both secondary sex characters (Oliveira and Almada, 1998) and male-male competitive behavior (i.e. winner effect, Oliveira et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, if androgen levels were a response to the acquired social status it would be predicted that only after group formation the correlation between androgen levels and social status would be present. Oliveira et al (1996) found that the latter hypothesis was the one supported by the data, which showed a lack of correlation between the androgen levels (both T and KT) prior to group formation and the social status achieved, but strong correlations between androgen levels (both T and KT) measured after group formation and the acquired social status.…”
Section: Androgen Levels Territorial Intrusions and Social Status Acmentioning
confidence: 74%
“…In trying to disentangle these two hypotheses Oliveira et al (1996) computed correlations between androgen levels and a social dominance index before and after group formation in the cichlid fish Oreochromis mossambicus. The rationale behind this experiment was that if androgen levels are the determining factors of social status acquisition then it would be expected that androgen levels before group formation would be good predictors of the social status that the individuals would acquire after group formation.…”
Section: Androgen Levels Territorial Intrusions and Social Status Acmentioning
confidence: 99%
“…hauser and Oliveira, 2000; lizards: Thompson and Moore, 1992; but see Houck and Woodley, 1995;teleosts: Cardwell and Liley, 1991;Pankhurst and Barnett, 1993;Oliveira et al, 1996Oliveira et al, , 2001cOliveira et al, , 2002mammals: Cavigelli and Pereira, 2000;Nunes et al, 2000; but see Creel et al 1993). Only the change to extremely high paternal investment (i.e., paternal incubation among the altricial passerines) contributed to the evolution of different androgen response rates.…”
Section: Discussionmentioning
confidence: 99%